Total volume and composition of fluid intake and mortality in older women: a cohort study. Issue 3 (24th March 2017) - Lim, Wai H; Wong, Germaine; Lewis, Joshua R; Lok, Charmaine E; Polkinghorne, Kevan R; Hodgson, Jonathan; Lim, Ee M; Prince, Richard L
Abstract : Objectives: The health benefits of 'drinking at least 8 glasses of water a day" in healthy individuals are largely unproven. We aimed to examine the relationship between total fluid and the sources of fluid consumption, risk of rapid renal decline, cardiovascular disease (CVD) mortality and all-cause mortality in elderly women. Design, setting and participants: We conducted a longitudinal analysis of a population-based cohort study of 1055 women aged ≥70 years residing in Australia. Main outcome measures: The associations between total daily fluid intake (defined as total volume of beverage excluding alcohol and milk) and the types of fluid (water, black tea, coffee, milk and other fluids) measured as cups per day and rapid renal decline, CVD and all-cause mortality were assessed using adjusted logistic and Cox regression analyses. Results: Over a follow-up period of 10 years, 70 (6.6%) experienced rapid renal decline and 362 (34.4%) died, of which 142 (13.5%) deaths were attributed to CVD. The median (IQR) intake of total fluid was 10.4 (8.5–12.5) cups per day, with water (median (IQR) 4 (2–6) cups per day) and black tea (median (IQR) 3 (1–4) cups per day) being the most frequent type of fluid consumed. Every cup per day higher intake of black tea was associated with adjusted HRs of 0.90 (95% CI 0.81 to 0.99) and 0.92 (95% CI 0.86 to 0.98) for CVD mortality and all-cause mortality, respectively. There were no associations between black tea intake and rapid renal decline, or between the quantity or type of other fluids, including water intake, and any clinical outcomes. Conclusions: Habitual higher intake of black tea may potentially improve long-term health outcomes, independent of treating traditional CVD risk factors, but validation of our study findings is essential.